High-speed data encryption and geoinformation system for monitoring forest fires for low-orbit aircraft - Bakyt, M.A.; Moldamurat, Kh.; Atanov, S.K.; Kalmanova, D. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2025)
The article considers the problem of ensuring the security of data obtained from low-orbit aircraft (LOA) when solving the problems of monitoring and forecasting forest fires. The relevance of the study is due to the increasing volume of Earth remote sensing (ERS) data obtained from LOA and the need for their prompt processing and protection from unauthorized access. An integrated approach is proposed, including the development of a high-speed data encryption system adapted to the limited computing resources of LOA and the creation of a geographic information system (GIS) for analyzing and interpreting ERS data. The GIS is equipped with modules for intelligent processing of aerospace images, allowing automatic detection of fire sources, modeling the dynamics of fire spread and assessing the affected area. Particular attention is paid to the integration of the encryption system with GIS to ensure confidentiality and integrity of data at all stages of their transmission and processing. The article presents the results of experimental verification of the proposed solutions, demonstrating their effectiveness and practical significance for forest fire monitoring.